Effect of dietary energy and polymorphisms in BRAP and GHRL on obesity and metabolic traits. (January 2018) - Imaizumi, Takahiro; Ando, Masahiko; Nakatochi, Masahiro; Yasuda, Yoshinari; Honda, Hiroyuki; Kuwatsuka, Yachiyo; Kato, Sawako; Kondo, Takaaki; Iwata, Masamitsu; Nakashima, Toru; Yasui, Hiroshi; Takamatsu, Hideki; et al.
Summary: Objective: Obesity, a risk factor for all-cause and cardiovascular mortality, is a major health concerns among middle-aged men. The aim of this study was to investigate a possible association of dietary habits and obesity related single nucleotide polymorphisms (SNPs) with obesity and metabolic abnormalities. Methods: We conducted a retrospective cohort study using annual health examination data of 5112 male workers, obtained between 2007 and 2011. Average dietary energy was estimated using electronically collected meal purchase data from cafeteria. We examined 8 SNPs related to obesity: GHRL rs696217, PPARG rs1175544, ADIPOQ rs2241766, ADIPOQ rs1501299, PPARD rs2016520, APOA5 rs662799, BRAP rs3782886, and ITGB2 rs235326. We also examined whether SNPs that were shown to associate with obesity affect other metabolic abnormalities such as blood pressure (BP), glucose, and lipid profile. Results: Average dietary energy significantly associated with increased abdominal circumference (AC) and body mass index (BMI). The odds ratios (ORs) of overweight and obesity also increased. The major allele of rs696217 significantly increased BMI and an increased OR with obesity, while the minor allele of rs3782886 was associated with significantly decreased AC and the decreased ORs with overweight and obesity. The minor allele of rs3782886 was also associated with significantly decreased systolic BP (SBP), triglyceride (TG), high-density lipoprotein (HDL), and fasting blood sugar (FBS), while rs696217 was not associated with other metabolic abnormalities. Conclusions: Average dietary energy in lunch, rs3782886, and rs696217 were associated with obesity, and rs3782886 was associated with other metabolic abnormalities.